Procedural Attack! Procedural Generation for Populated Virtual Cities: A Survey - Werner Gaisbauer; Helmut Hlavacs (Serious Games Society, 2017)
On the one hand, creating rich virtual worlds "by hand" like in the game Grand Theft Auto V is hugely expensive and limited to large studios. On the other hand, procedural content generation (PCG) allows tiny teams to create huge worlds like Hello Games did with only four people (in the beginning) for the recently released game No Man's Sky. Following in the footsteps of Hello Games, this paper tries to equip the reader with an overview about the state-of-the-art of how to build such a virtual world, i.e., a populated virtual city with buildings, streets, parks, vegetation, humans, and vehicles, using just PCG assets. Each PCG asset that is envisioned to bring the city to life is grouped and discussed in detail and the latest research trends in PCG are presented together with open questions. Using the above-mentioned PCG assets, instead of months, a city can be built in a mere couple of minutes by a user without much experience in designing 3D assets. The city can then be used for many applications like games, virtual reality (VR), or film.